LAMA FERMENTASI TERHADAP KADAR SERAT NATA BUAH GANDARIA - Juen Carla Warella; Pamella Mercy Papilaya; Prelly Tuapattinaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Gandaria fruit on the island of Ambon has benefits if the sale value can be used as raw material for the manufacture of Nata products. The making of Nata Gandaria fruit with the help of Acetobacter xylinum microorganisms, the role of microbes to break down glucose into cellulose or fiber that is important for the human body. Methods: To know the length of fermentation to know the effect of fiber content of Gandaria nata, then tested on fiber content of nata Gandaria fruit that has been fermented for 10 days and 12 days. Result: Based on the test results using gravimetry fiber content method known nata fermentation time can increase fiber content. The highest increasing fiber content at nata occurred on day 12 with an average fiber content of 0.45% and the lowest occurred on fermentation day 10 with an average fiber content of 0.35%. Conclusion: The duration of fermentation has an effect on the fiber content of gandaria fruit (Bouea macrophylla griff). The duration of fermentation that produces gandaria fruit nata (Bouea macrophylla griff) with the highest fiber content is on the 12th day while the fermentation time that produces the gandaria fruit (Bouea macrophylla griff) with the least fiber content is the 10th day